1988
DOI: 10.1093/nar/16.24.11781
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the recognition mechanism involved in the EcoRV catalyzed cleavage of DNA using modified oligodeoxynucleotides

Abstract: We have prepared a series of undecadeoxynucleotides that contain changes in the functional group pattern present within the EcoRV recognition site - GATATC-. Oligonucleotides were synthesized on solid phase using normal and modified beta-cyanoethylphosphoramidites and analyzed in steady state cleavage experiments with the EcoRV restriction endonuclease. The following groups appear to interact strongly with the enzyme, since their modification or substitution renders the oligonucleotides refractory to cleavage:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 71 publications
4
39
0
Order By: Relevance
“…The EcoRV -DNA interface and in particular the recognition contacts have been probed with modified DNA substrates (Fliess et al, 1988;Mazzarelli et al, 1989;Newman et al, 1990) and with mutant proteins (Thielking et al, 1991;. There is very satisfactory agreement in the sense that modifications which directly perturb the observed interactions produce large reductions in the cleavage rates.…”
Section: Discussionmentioning
confidence: 92%
“…The EcoRV -DNA interface and in particular the recognition contacts have been probed with modified DNA substrates (Fliess et al, 1988;Mazzarelli et al, 1989;Newman et al, 1990) and with mutant proteins (Thielking et al, 1991;. There is very satisfactory agreement in the sense that modifications which directly perturb the observed interactions produce large reductions in the cleavage rates.…”
Section: Discussionmentioning
confidence: 92%
“…These analogues gave excellent substrates with kinetic properties very similar to the parent. Previously, it has been observed that dSMeC or the isosteric 5-bromodeoxycytidine gave good substrates for the endonuclease (Fliess et al, 1988). However, the role of the 4-amino group of dC has not been probed using analogues.…”
Section: ~( P G a C [~~~P ] A T A T C G T C )mentioning
confidence: 99%
“…Previous reports have shown that some restriction enzymes can recognize and cleave many chemically modified DNA substrates with certain hydrolysis efficiency . In most, if not all, of these cases, the modifications involving either base or sugar‐phosphate backbone tolerated by the restriction enzymes were induced on a single strand, rather than both strands, of the recognition site .…”
Section: Discussionmentioning
confidence: 99%
“…Binding to the specific recognition site with suitable flanking sequences will then activate the restriction enzyme by increasing catalysis . Synthetic modified oligodeoxyribonucleotide duplexes have been applied to probe the DNA determinants required for such a recognition by a series of restriction enzymes . The success of this approach depends mostly on the availability of a large number of suitably modified DNA substrates.…”
Section: Introductionmentioning
confidence: 99%